David et Goliath : L’équilibre fragile des relations énergétiques canado-américaines à l’aube de la création de Petro-Canada - Jacomy-Millette, Annemarie (Études internationales)

(untitled) (Institut québécois des hautes études internationales, 1982)
During the 1970's and at the dawn of the 80's, the intervention of the Federal Government of Canada in the country's economic sector became more pronounced, thus following a Worldwide trend in that aspect. It is specially marked in the sector of energy where it supports the Canadianization objectives which run counter to foreign interests and investments, first and foremost american. This article gives an idea of the world context in which lies the choice for energy policies. It goes on to de scribe the evolution of these policies which firmly hinge on the North-South continental context. The objectives outlined in the National Energy Program cannot allow to ignore this essential variable, specially in the determination of means and measures to be used to further economic nationalism. Such are the pressures brought about, at the highest level, by the american administration under the presidency of Ronald Reagan.